Implementation of Money Wakaf In Man 1 Medan City (R&D Study Of Islamic Religious Education Learning Module) - Nasution, Mayurida; Nasution, Wahyudin Nur; Mardianto, Mardianto (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The objectives of this study are: 1). To analyze the effectiveness of the development of cash waqf materials in MAN 1 Medan city, 2). To analyze the design of the cash waqf learning module at MAN 1 Medan city, 3). To implement cash waqf in MAN 1 Medan city based on the Islamic Religious Education learning module. The research method used is Research And Development (R&D). The results of this study are that researchers create product types of cash waqf modules and E-Mobile-based waqf applications that are named E-Cash Waqf which can be downloaded on Playstore. First, research on the development of cash waqf materials through modules at MAN 1 Medan City is very effective. Second, the design of teaching materials for cash waqf material through validation results averaged 87.18%, in terms of presentation an average of 97.91%, language aspects averaged 75% and design validation averaged 82.29% and IT validation with an average of 93.11%. Third, the implementation of cash waqf materials based on modules developed based on e-mobile found results starting from the pre-test of 77.84% while the results of the post-test were 91.23%. From the studies conducted, it can be recommended that innovation through e-modules that are developed greatly influence the learning outcomes of students. They also find a novelty about cash waqf material in the form of applications available on PlayStore.